Improvement of Activeness and Learning Outcomes of English Speaking through the Snowball Throwing Learning Model - Molla, Nur Laila (Jurnal Bahasa Inggris, 2020)
This research focused on the aspect of speaking skills of the students of Molla Course Tegal where the students' English speaking ability was still quite low. Implementation of Snowball Throwing cooperative learning model was conducted using the Classroom Action Research (CAR). The research subjects were 22 students. The indicator of success was Minimum Completeness Criteria (KKM) that was 75. Standard percentage of classical completeness was 80%. In pre-cycle, the result of activeness observation was 22.15% with low criteria. In the first cycle, percentage of activeness increased 39.21%, so that percentage of activeness became 61.36% with high criteria. In the second cycle, activeness increased by 35.79% to 97.15% with very high criteria. The increase in student learning outcomes shows that in cycle I, from 22 students there were 16 students or 72.72% of students who have reached completeness score, while 6 students or 27.27% have not yet achieved completeness. The average score in the first cycle was 76.39. In cycle II, the deficiencies were corrected; 22 students (100%) obtained complete learning outcomes with average score of 90.02. Results of the study prove that Snowball Throwing Model increases learning activeness and English speaking skills.